KEPATUHAN PELAPORAN PAJAK PENGHASILAN TAHUNAN ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA PENJARINGAN TAHUN 2015-2016 - Edy Edy; Yanuar Adi Putra; Desti Riyanti (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
This final paper report discusses about (1) Compliance Rate of Personal Taxpayer Reporting in the Annual Tax Return Report of 2015 Up To 2016 Tax in Primary Tax Office Penjaringan, (2) Attempts made by Primary Tax Office Penjaringan To Improve Compulsory Compulsory Individual Taxes in Annual Reports of SPT. The method used qualitative and using interview and observation techniques. The results of the complaint refer to (1) Compliance Rate of Private Taxpayer Reporting in Annual Income Tax Reporting of 2015 Up to 2016 Income Tax in Primary Tax Office Penjaringan is 78.63% and 68.14% indicating that there is a decrease, (2) Efforts made by the Tax Office Primary Penjaringan To Increase Personal Taxpayer Compliance in Reporting Annual SPT by socializing taxes, realizing tax census, providing dropbox.